Alternatif Penyelesaian Sengketa Luar Hukum Bagi Inventor Terhadap Pelanggaran Moral Hak Cipta Lagu Dalam Hak Ekonomi - Yapiter Marpi (PT PUSTAKA CENDEKIA GROUP, 2024)
Copyright is an exclusive right that gives rewards to the creator in the form of economic rights and moral rights. Moral rights are rights inherent in the creator's personality which are basically carried out to respect the creator's creativity by including his name in the creative work. Legal protection for musicians regarding copyright in paying royalties as well as resolving disputes regarding the use of song works without paying royalties. Easy access to information and technology often provides opportunities for netizens to access copyrighted works without including the name of the creator. In this research, there are two problems examined, namely moral rights in the copyright protection system and resolution of moral rights disputes in copyrighted works. Moral rights consist of the right for the creator to continue to include or not include his name on the copy in connection with the use of his work for the public, to use his alias or pseudonym, to change his work according to appropriateness in society, to change the title and sub-title of the work; and defend their rights in the event of distortion of the Work, mutilation of the Work, modification of the Work, or anything that is detrimental to their personal honor or reputation. To protect the moral rights of the Creator may have Copyright management information; and/or Copyright electronic information. The results of the research show that there is still no awareness among artists. Even national performances are still not aware of copyright so there needs to be a real role for the relevant government to be more active in monitoring and providing real protection. Settlement of disputes over violations of moral rights in copyrighted works can be done through. dispute resolution, arbitration, or court. Supervision is needed to see what is happening in the field so far, there must be clarity regarding the relevant regulations and there also needs to be a clear agreement so that there is mutual benefit and there are no misunderstandings in the future.